INOVASI TEKNOLOGI TEPAT GUNA ALAT PENABUR PUPUK UNTUK MENINGKATKAN PRODUKTIVITAS PERTANIAN DI DESA ROWOBONI - Mahasiswa Yuhanda; Fairuz Miksalmina; Ata Farzana Meisy Naulintya; Nuri Yuthika Febriyanti; Mukhtarul Huda; Shofwatun ‘Afiyah; Eva Nurhida Maulidha; Lubnaya Nabigha (Departemen Teknologi Pertanian Universitas Hasanuddin, 2026)
An appropiate technology innovation in the form of a simple fertilizer spreader has been introduced to farmers in Rowoboni Village through the Community Service Program (Kuliah Kerja Nyata, KKN) of UIN Walisongo Semarang. This tool is designed using easily accessible and affordable materials, such as PVC pipes, with the aim of facilitating the fertilization process in agricultural fields. The implementation method includes nees observation, tool design, construction, and demonstration to farmers in two hamlets. The result of the implementation showed a positive response from the farmers, who experienced time efficiency, labor savings, and more even fertilizer distribution. This innovation has proven to improve agricultural productivity and reduce farmer’s worklod, thus having the potential to provide sustainable. Keywords: Innovation, Tool, Fertilization